1998
DOI: 10.1080/096031098332637
|View full text |Cite
|
Sign up to set email alerts
|

The causes of stock market volatility in Australia

Abstract: The paper examines the extent to which the conditional volatility of stock market returns in a small, internationally integrated stock market are related to the conditional volatility of financial and business cycle variables. It employs a low frequency monthly dataset for Australia including stock market returns, interest rates, inflation, the money supply, industrial production and the current account deficit over the period from July 1972 to January 1994. A novel feature of the analysis is the estimation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 31 publications
3
35
0
1
Order By: Relevance
“…This is in agreement with the studies of Geske and Roll (1983), Chen, Roll and Ross (1986), Fama (1990), Kearney and Daly (1998), and Maysami & Koh (2000) Maghayereh (2002), Al-Sharkas (2004).…”
Section: Empirical Results and Interpretationssupporting
confidence: 93%
“…This is in agreement with the studies of Geske and Roll (1983), Chen, Roll and Ross (1986), Fama (1990), Kearney and Daly (1998), and Maysami & Koh (2000) Maghayereh (2002), Al-Sharkas (2004).…”
Section: Empirical Results and Interpretationssupporting
confidence: 93%
“…In contrast to empirical evidences discussed in above literature, there are also studies that reported no evidence of flow of volatility between stock market and foreign exchange market, see (Apergis and Rezitis 2001;Kearney and Daly 1998;Morales 2008). Apergis and Rezitis (2001) extended the literature for New York and London and found no evidence of volatility transmission between currency and stock market.…”
Section: Review Of Literaturementioning
confidence: 77%
“…Morales (2008) empirically studied Six Latin American countries; Venezuela, Argentina, Mexico, Brazil, Colombia and Spain with a European country and found no clear evidence of flow of volatility between the two financial markets. Kearney and Daly (1998) tested the stated relationship for Australia and found no evidence of volatility flow between currency market and stock market.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In Bangladesh, flow of cash is not generally based on past profit and thus the credit markets have greater impact on the retained earnings of the firms. Kearney and Daly (1998) examines the extent to which the conditional volatility of stock market returns in a small, internationally integrated stock market are related to the conditional volatility of finance and business cycle volatility. It employs a low frequency monthly dataset for Australia including stock market returns, interest rates, inflation, the money supply, industrial production and the current account deficit.…”
Section: Literature Reviewmentioning
confidence: 99%